Investigation of the molecular signatures of selection on ATP synthase genes in the marine bivalve Limecola balthica - Pante Eric; Becquet Vanessa; Viricel Amélia; Garcia Pascale (Aquatic Living Resources, 2019)
We used transcriptomic sequence data to describe patterns of divergence and selection across different populations of a marine bivalve (Limecola balthica). Our analyses focused on a nuclear gene (atp5c1) that was previously detected in an FST scan as highly structured among populations separated by the Finistère Peninsula in France. This gene encodes the gamma subunit of the FO/F1 ATP synthase, a multi-protein complex that is paramount to cellular respiration and energy production. Analysis of non-synonymous to synonymous mutation ratios revealed that 65% of the gene is highly conserved (dN/dS ≤ 0.1, min = 0), while 6% of the gene is likely under positive selection (dN/dS ≥ 1, max = 2.03). All replacement mutations are clustered on a 46 residues portion of the protein, within an inter-peptide interaction zone. Comparative genomics suggests that these mutations are evolutionarily stable, and we hypothesize that they are involved in inter-population genetic incompatibilities with other subunits of the ATP synthase complex. The protein stability of the gamma subunit conferred by southern variants was inferred to be higher under warmer temperatures, suggesting that environmental conditions may contribute to the strength of genetic barriers in L. balthica.